2009
DOI: 10.1016/j.visres.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Space information is important for reading

Abstract: Reading a text without spaces in an alphabetic language causes disruption at the levels of word identification and eye movement control. In the present experiment, we examined how word discriminability affects the pattern of eye movements when reading unspaced text in an alphabetic language. More specifically, we designed an experiment in which participants read three types of sentences: normally written sentences, regular unspaced sentences, and alternatingbold unspaced sentences. Although there was a reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
100
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 27 publications
12
100
2
1
Order By: Relevance
“…Rayner et al 1998). What is inconsistent with the literature is that in previous studies, the first appearance of this interaction has been consistently reported in gaze duration (Perea & Acha, 2009;Rayner et al, 1998;Sheridan et al, 2013;Sheridan et al, 2016;Veldre et al 2016), whereas this interaction was not close to significant for gaze durations in the current study. The absence of this interaction was even more surprising given the sizeable numerical interaction in the untransformed gaze durations (91ms frequency effect in unspaced compared to 41 ms in spaced reading).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Rayner et al 1998). What is inconsistent with the literature is that in previous studies, the first appearance of this interaction has been consistently reported in gaze duration (Perea & Acha, 2009;Rayner et al, 1998;Sheridan et al, 2013;Sheridan et al, 2016;Veldre et al 2016), whereas this interaction was not close to significant for gaze durations in the current study. The absence of this interaction was even more surprising given the sizeable numerical interaction in the untransformed gaze durations (91ms frequency effect in unspaced compared to 41 ms in spaced reading).…”
contrasting
confidence: 99%
“…These findings, both the increased frequency effect in unspaced compared to spaced reading, and the time course of the effect in that it appears in gaze duration and not earlier, has been replicated multiple times (e.g. Perea & Acha, 2009;Sheridan, Rayner & Reingold, 2013).Additionally, using survival analyses, Sheridan et al (2013) were able to show a later time course of word frequency effects in unspaced versus spaced reading. They observed the earliest discernible influence of word frequency in spaced text 112 ms from the start of fixation, with no discernible difference until 152 ms into the fixation when the text was unspaced.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In a recent study, Perea and Acha (2009) found reading cost in unspaced sentences relative to normally written sentences, with smaller cost for sentences with words presented in an alternating bold-normal unspaced series than for sentences with words presented as a regular unspaced series. These results indicate that readers can use other information than an empty space to determine word boundaries for target selection.…”
Section: Discussionmentioning
confidence: 93%
“…As such, it is crucial that when we read a line of text, we are able to identify the beginnings and endings of individual lexical items, a process referred to as word segmentation. A number of studies have reported substantial reductions in reading rate for English text when interword spaces are removed (Morris, Rayner, & Pollatsek, 1990;Perea & Acha, 2009;Pollatsek & Rayner, 1982;Rayner, Fischer, & Pollatsek, 1998;Rayner, Yang, Schuett, & Slattery, 2013;Sheridan, Rayner, & Reingold, 2013;Spragins, Lefton, & Fisher, 1976). However, at least one study has reported a more modest reduction in reading rate for text without spaces (Epelboim, Booth, & Steinman, 1994).…”
Section: Interword Spacing Effectsmentioning
confidence: 99%